PHILOSOPHICAL AND LEGAL DIMENSION OF LEGAL STATE - Бородін, Іван Лук'янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: is to make the systematic, sequential analysis of the philosophical-legal thought on issues of natural law, a social agreement, a civil society, the principles of separation of power that are the fundamental ideas related to the definition of a legal state. Methods: phenomenological, comparative-legal, sociological, logical, dialectical, formally dogmatic. Results: an attempt has been made to clarify the understanding of a legal state through the analysis of the philosophical-legal thought of the best representatives of various civilizations, the argumentation of the provision on the mutual conditioning of the socio-regulatory functions of a state, its optimal influence on the process of formation and expansion of a civil society. Discussion: the real and cognitive processes of creation and evolution of the ideas of a legal state which are at every stage of the civil society’s development reflect the corresponding level of culture and the real legal reality of a country and the world in a whole.